Water Use in the Latoritsa River Basin: Condition and Optimization - Лета, В. В.; Микита, М. М.; Салюк, М. Р.; Фекета, І. Ю.; Мельничук, В. П. (Київський національний університет імені Тараса Шевченка, 2022)
The urgency of constructive-geographical analysis of water use within the upper part of the basin of the river Latorytsia is substantiated. In the materials of the article the water-resource and morphometric characteristics of the rivers of the upper part of the Latorytsia river basin are analyzed. The main works of domestic scientists and practitioners in the field of hydrology, hydromorphology and hydroecology, which relate to rivers within the Latoritsa basin in the Transcarpathian region, are considered. The stock materials of the Transcarpathian Center for Hydrometeorology, the Tisza River Basin Department and the Department of Ecology and Natural Resources of the Transcarpathian Regional State Administration were collected and processed. A brief description of the hydrological parameters of Upper Latorytsia is given. Based on a statistical series of data, the structure and dynamics of water use within the Latorytsia river basin from its source to Mukachevo for the period from 1990 to 2020 were studied in detail. Statistical samples of such water use indicators as total water users, intake use of water in general and for individual water management purposes, volumes of discharged water in general and by certain categories, water losses during transportation, etc. The state and performance of sewage treatment plants of the largest water users within the studied part of the Latoritsa basin are considered separately: volumes of water discharge by different categories and types of treatment. The main trends, characteristics, changes in the structure, needs and dynamics of water use indicators within the upper part of the Latorytsia river basin over a 30-year period have been identified. The impact of the main surface water pollutants in the Latoritsa basin, including utilities and recreational facilities, was analyzed. Initial data from the Tisza River Basin Management were used to build a map of the river network of the Latorytsia river basin within the Transcarpathian region and a map of the location of the main water users within the upper part of the Latorytsia river basin. Based on the study, including a detailed analysis of 2-TP water management reports, a number of water management problems were identified and ways to solve them, as well as measures to optimize water use within the Latoritsa basin system to reduce anthropogenic pressure on surface water bodies and improve their environmental state.

В матеріалах статті проаналізовано водно-ресурсні та морфометричні характеристики річок верхньої ділянки басейну річки Латориця. Зібрано та опрацьовано фондові матеріали Закарпатського центру з гідрометеорології, Басейнового управління водних ресурсів річки Тиса та Департаменту екології та природних ресурсів Закарпатської ОДА. На основі статистичного ряду даних детально вивчено структуру та динаміку водокористування в межах ділянки басейну річки Латориця від витоку до м. Мукачево за період з 1990 р. по 2020 р. Проаналізовано статистичні вибірки таких показників водокористування, як загальна кількість водокористувачів, об’єми забору та використання вод загалом та на окремі водогосподарські цілі, об’єми скинутих вод загалом та за окремими категоріями, втрати вод при транспортуванні тощо. Проаналізовано вплив основних забруднювачів поверхневих вод басейну Латориці, зокрема комунальних підприємств та об’єктів рекреації. На основі проведеного дослідження, зокрема детального аналізу водогосподарських звітів 2-ТП, виявлено ряд водогосподарських проблем і напрацьовано шляхи їх вирішення, а також заходи з оптимізації водокористування в межах басейнової системи Латориці з метою зменшення антропогенного навантаження на поверхневі водні об’єкти та покращення їх екологічного стану.
Водокористування у басейні річки Латориця: стан та оптимізація
Keywords: Верхня Латориця; динаміка використання вод; стан водного господарства; оптимізація водокористування; Upper Latorytsia; dynamics of water use; state of water management; water use optimization.